Official voices of a revolution: a social history of Islamic republican poetry - Shams-Esmaeili, F (2015)
This thesis is primarily concerned with the literary aspects of the Islamic Republic of Iran. Its immediate focus rests on the evolution of the Islamic republican poetic trend, encompassing both the disillusioned and conformist voices that rose to prominence in the course of the 1979 Revolution and their on-going engagement with the ruling political power. In this vein, this thesis investigates the various cultural policies of the state, as well as select political transformations of the past three decades, all of which played a pivotal role in this literary evolution. The thesis shows how the official poets that emerged during the 1979 Revolution, and which proved significantly active throughout the immediate history subsequent to that event (war with Iraq, the death of Ayatollah Khomeini and the rise and fall of the reform movement), evolved over time and thereby either received political support for their commitment to the state ideology or became gradually excluded from official cultural institutions. Finally, this thesis reviews the manner in which state strategies have shaped an institutionalised form of poetry that is monitored and reinforced by the Supreme Leader of the Islamic Republic and official cultural authorities. It demonstrates how an innate linking of the project of Islamic republican literature to underlying ideologically defined notions such as 'religious verse', 'legitimate poetry' and 'commitment' was and continues to be an intrinsic part of the literary foundations of the ideological apparatus of the Islamic Republic.